2008
DOI: 10.1007/s11295-007-0119-8
|View full text |Cite
|
Sign up to set email alerts
|

Origin of resistance to plum pox virus in Apricot: what new AFLP and targeted SSR data analyses tell

Abstract: Amplified fragment length polymorphisms (AFLP) and targeted simple sequence repeats (SSR) were employed to assess genetic similarity of North American apricots having natural resistance to plum pox virus (PPV) within diversified germplasm including six nondomesticated apricot species. On a dendrogram constructed from 231 AFLP loci, the position of the North American cultivars reflects relatedness to the European apricots and introgression of non-European germplasm as well. The occurrence of diagnostic AFLP mar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
35
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 55 publications
2
35
0
Order By: Relevance
“…This topic has been reviewed by Zhebentyayeva et al [29]. All apricot cultivars of European origin are susceptible to PPV.…”
Section: Kostina Et Al Compared the Inheritance Of Dormancy Length Imentioning
confidence: 99%
“…This topic has been reviewed by Zhebentyayeva et al [29]. All apricot cultivars of European origin are susceptible to PPV.…”
Section: Kostina Et Al Compared the Inheritance Of Dormancy Length Imentioning
confidence: 99%
“…Hormaza (2002) also demonstrated that Chinese cultivars contributed to the pedigree of 'Stark Early Orange'. The recent research of Zhebentyayeva et al (2008) shows that cultivars 'Harlayne', 'Goldrich', and 'Stark Early Orange' has genetic similarity with native Central Asian genotypes. The researchers also showed that Prunus davidiana alleles in 'Stark Early Orange' and Prunus mume alleles in 'Stark Early Orange' and 'Goldrich' pointed out a contribution of these species to PPV resistance as well (Zhebentyayeva et al 2008).…”
Section: Sharka (Plum Pox Virus) Resistance In Genetic Diversity Of Amentioning
confidence: 99%
“…Previous study indicates that this PPV resistance mechanism might have been directly or indirectly introduced from non-domesticated species found in China, for example P. sibirica, P. mandshurica, P. mume, P. sibirica var. davidiana and wild accessions of P. armeniaca (Zhebentyayeva et al 2008). These few sources of resistance share a similar or genetically close progenitor, originating presumably from Northern China (Zhebentyayeva et al 2008).…”
mentioning
confidence: 99%
“…davidiana and wild accessions of P. armeniaca (Zhebentyayeva et al 2008). These few sources of resistance share a similar or genetically close progenitor, originating presumably from Northern China (Zhebentyayeva et al 2008). This limited genetic base for resistance is expected to jeopardize the development of durable and stable resistance to PPV in fields.…”
mentioning
confidence: 99%
See 1 more Smart Citation